Severe alpha-1 antitrypsin deficiency is associated with a higher risk of complications after first decompensation than other aetiologies of cirrhosis - Balcar, Lorenz; Fromme, Malin; Kappe, Naomi; Schaefer, Benedikt; Fraňková, Soňa; van Melkebeke, Lukas; Stolk, Jan; Jachs, Mathias; Semmler, Georg; Hofer, Benedikt S; Tergast, Tammo L; Rieland, Hannah; et al. (JHEP reports, 2025)
BACKGROUND & AIMS: Alpha-1 antitrypsin deficiency (AATD) causes/predisposes to advanced chronic liver disease. However, the role of the SERPINA1 Pi∗ZZ genotype in patients with decompensated cirrhosis is unclear. Thus, we evaluated the impact of the Pi∗ZZ genotype on the disease course after the first hepatic decompensation event. METHODS: We retrospectively included 59 adults with decompensated cirrhosis and severe AATD (Pi∗ZZ) from 12 European tertiary care centres. First decompensation was considered as baseline. To compare the course of AATD to other cirrhosis aetiologies, we applied propensity score matching for Child-Turcotte-Pugh (CTP) score as well as age/sex. Patients were followed until further decompensation, liver transplantation or liver-related death. RESULTS: Most patients were male (74.6%), with a mean age of 55 years. The most common type of first decompensation was ascites (n = 40; 67.8%), followed by variceal bleeding (n = 13; 22.0%) and overt hepatic encephalopathy (n = 6; 10.2%). Median CTP and MELD (model for end-stage liver disease) scores at first decompensation were 8 and 14, respectively. Median MELD scores were 16 and 20 points at listing and liver transplantation (median time on list: 2.9 [IQR 1.1-7.2] months), respectively. Patients with other aetiologies (subdistribution hazard ratio: steatotic liver disease: 0.62, 95% CI 0.44-0.88, p = 0.007; abstinent alcohol-associated liver disease: 0.50, 95% CI 0.35-0.71, p <0.001; hepatitis C virus-associated cirrhosis: 0.56, 95% CI 0.37-0.83, p = 0.004) had a significantly lower risk of further hepatic decompensation, liver transplantation, or liver-related death, compared to those with Pi∗ZZ. Exchanging further decompensation with acute-on-chronic liver failure yielded similar results. CONCLUSION: Our study defines the course of decompensated cirrhosis in patients with severe AATD (Pi∗ZZ), who are particularly prone to complications of cirrhosis and exhibit a more progressive disease course than those with cirrhosis of other aetiologies. IMPACT AND IMPLICATIONS: Alpha-1 antitrypsin deficiency is an inherited disease that affects the lung and the liver. Carrying two severely dysfunctional copies of the alpha-1 antitrypsin gene may cause advanced chronic liver disease/cirrhosis. Affected individuals with a first complication of cirrhosis are more prone to developing further liver-related events (including multiorgan dysfunction) and requiring liver transplantation (which cures the inherited liver disease) compared to patients who have similarly advanced liver disease. These findings should prompt the development of disease-modifying treatments and early listing for liver transplantation.
Keywords: ascites; advanced chronic liver disease; hepatic encephalopathy; portal hypertension; liver transplantation; variceal bleeding; AATD; acute-on-chronic liver failure